SARS‐CoV‐2‐related Multisystem Inflammatory Syndrome in Adult complicated by myocarditis and cardiogenic shock. (31st August 2022) - De Smet, M.A.J.; Fierens, J.; Vanhulle, L.; Vande Weygaerde, Y.; Malfait, T.L.A.; Devos, D.; Haerynck, F.; Gevaert, S.
Abstract: Multisystem Inflammatory Syndrome in Adult (MIS‐A) is a rare COVID‐19 complication, presenting as fever with laboratory evidence of inflammation, severe illness requiring hospitalization and multisystem organ involvement. We report on a 25‐year‐old man presenting with fever, rash, abdominal pain, diarrhoea and vomiting following prior asymptomatic COVID‐19 infection. He developed refractory shock and type 1 respiratory insufficiency requiring mechanical ventilation. Diagnostic testing revealed significant inflammation, anemia, thrombocytopenia, acute kidney injury, hepatosplenomegaly, colitis, lymphadenopathy and myocarditis necessitating inotropy. Ventilatory, vasopressor and inotropic support was weaned following pulse corticosteroids and intravenous immunoglobulins. Heart failure therapy was started. Short‐term follow‐up shows resolution of inflammation and cardiac dysfunction.